The capability of [multi-rotor DJI phantom 3] advanced for detecting crack on concrete wall different distance / Ain Uzzairah Amran - Amran, Ain Uzzairah (2018)
Distance plays an important role in determining the crack detection where without proper or fixed value of distance, the time taken to capture image of crack is increased. It is important to know the capability of multi-rotor DJI Phantom 3 at different distance for detecting crack as the maximum distance may be useful for next buildings inspection where it shorten the time taken to inspect crack on the buildings. This paper provides the capability of multi-rotor DJI Phantom 3 for detecting crack at different distance. This study has been constructed by considered to three objectives that need to be achieved at the end of this research. The three objectives are to identify crack width of the study area, to study the relationship of distance affected the size of detectable crack by quantitative and qualitative measures and to access the accuracy of multi-rotor DJI Phantom 3 in detecting crack at different distance measurement. In this study covered four parts of methodology including planning and reconnaissance, data acquisition or collection, data processing and data analysis. Data processing is divided into two parts which using Agisoft software and Digimizer software. The accuracy assessment is used in order to analyze capabilities of multi-rotor DJI Phantom 3 in detecting crack at different distance. The qualitative measures uses edge detection algorithm of Digimizer software to detect crack whereas quantitative uses accuracy assessment with edge detection algorithm to study their relationship. The capabilities of multi-rotor DJI Phantom 3 in detecting crack at different distance is identified where hairline crack is visible at 3 meter, narrow crack at 5 meter, medium crack at 6 meter and 10 meter at wide crack.